RNAinterference Identifies Genes Important for Cilia Structure and Function - Braunreiter, Kara; Gabrhel, Casey (My University, 2012)
Primary cilia are cellular antennae that mediate responses to the external environment. Response requires perception of a cue and transmission of that signal to the cell. This study employed a reverse genetic strategy known as RNAinterference to systematically reduce the function of each gene chromosome I and examine the effects on PKD-2 localization in C. elegans. Once the genes have been identified that affect PKD-2 localization, the role of these genes in cilia structure and function will be examined.
Color poster with text, images, and charts.
Keywords: RNA; Genes--Identification; Cilia and ciliary motion; Posters